ЖУРНАЛИСТ ДӨРЕТИЎШИЛИГИНДЕ ПЕРИФРАЗАЛАРДЫҢ ХЫЗМЕТИ - Пирниязова, А.К.; Каллибекова, Г.П. (FAN va JAMIYAT, 2023)
The article is devoted to one of the figurative and expressive means - paraphrases used in the periodical press. Paraphrases of the language of newspapers are analyzed and divided into eleven thematic groups.